2006
DOI: 10.1103/physrevlett.96.081301
|View full text |Cite
|
Sign up to set email alerts
|

Leptogenesis from Gravity Waves in Models of Inflation

Abstract: We present a new mechanism for creating the observed cosmic matter-antimatter asymmetry which satisfies all three Sakharov conditions from one common thread, gravitational waves. We generate lepton number through the gravitational anomaly in the lepton number current. The source term comes from elliptically polarized gravity waves that are produced during inflation if the inflaton field contains a CP-odd component. The amount of matter asymmetry generated in our model can be of realistic size for the parameter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
407
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(415 citation statements)
references
References 12 publications
8
407
0
Order By: Relevance
“…The amplitude of gravitational waves gives the Hubble curvature during inflation and would tell us the value of the inflation potential [15]. In addition gravitational waves produced during inflation can have several applications like leptogenesis by the gravitational spin-coupling to neutrinos [16] or by a gravitational Chern-Simon coupling of the lepton number current [17]. Observation of the B-mode polarization in the CMB would confirm the existence of primordial super-horizon gravitational waves.…”
mentioning
confidence: 88%
“…The amplitude of gravitational waves gives the Hubble curvature during inflation and would tell us the value of the inflation potential [15]. In addition gravitational waves produced during inflation can have several applications like leptogenesis by the gravitational spin-coupling to neutrinos [16] or by a gravitational Chern-Simon coupling of the lepton number current [17]. Observation of the B-mode polarization in the CMB would confirm the existence of primordial super-horizon gravitational waves.…”
mentioning
confidence: 88%
“…CS modified gravity theories have been studied as models for parity violation [5] and leptogenesis [6], [7] in the early universe. CS models have also been used as effective theories where the CS term is radiatively generated via fermions coupling to gravity in a parity violating way [8].…”
Section: A Brief Review Of Cs Modified Gravitymentioning
confidence: 99%
“…where γ is defined in (14). The relations (13) have been derived in [8] and for brevity we do not repeat the derivation here.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of the model were carried out for example in [11], where the cosmic no-hair theorem is tested within Gauge-flation with a Bianchi I background, in [12], where the background solutions of Gauge-flation were explored, and in [13], where it is shown that the theory can be embedded in the gravi-leptogenesis scenario of [14]. Recently, it was also shown [15,16] that Gauge-flation shares some background trajectories with Chromo-natural inflation [17], another recent model which assigns to non-Abelian gauge fields a crucial role in the dynamics of inflation and in the generation of primordial fluctuations (see [6] for a comprehensive review).…”
Section: Introductionmentioning
confidence: 99%